Transformative Thanatology and Mesatya Politics: Reconstructing Kumbakarna's Heroism in Contemporary Balinese Shadow Puppet Theatre - Wicaksana, I Dewa Ketut; Wicaksandita, I Dewa Ketut; Prasetya, Hanggar Budi; Hinzler , Hedwig Ingrid Rigmodis (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This study re-examines the paradigm of heroic death in traditional performing arts through the Kumbakarna Lina (The Death of Kumbakarna) episode of Balinese shadow theatre as a dialectical locus between local values and global discourses. Employing an interpretive-hermeneutic approach, it integrates Balinese Hindu cosmology with Heidegger’s concept of Being-towards-death, Festinger’s theory of cognitive dissonance, and Schechner’s notion of restored behavior. Data were collected through participatory observation, visual documentation, textual analysis of the Kakawin Rāmāyana, and interviews with puppet masters and cultural practitioners. The findings highlight three contributions: (1) the conceptualization of transformative thanatology, positioning death as moral-cosmic integration; (2) the articulation of mesatya as a political-spiritual resistance principle transcending genealogical loyalty; and (3) the transformation of sacred narratives from textual media to contemporary performance and digital platforms, raising ethical concerns of authenticity. These insights enrich cross-cultural studies of death, heroism, and performance while offering practical implications for preserving and adapting tradition in the global era.